Relevansi Deep Learning Dalam Pendidikan Pesantren: Pendekatan Meaningful, Mindful, dan Joyful Learning - Wafi, Abdul; Soraya, Irma; Kurjum, Mohammad (al-Urwatul Wutsqo : Jurnal Ilmu Keislaman dan Pendidikan, 2025)
One of the approaches considered relevant in addressing the challenges of 21st-century education is deep learning, which emphasizes deep understanding, active engagement, and intellectual transformation. This approach comprises three main pillars: meaningful learning, mindful learning, and joyful learning, which are explored and analyzed in relation to their relevance within the learning practices of pesantren—traditional Islamic educational institutions known for their distinctive pedagogical heritage. This study employs a qualitative approach using the library research method, analyzing primary and secondary literature from various reputable academic sources. The data were analyzed using thematic analysis to identify the core characteristics of deep learning as reflected in pesantren practices, including the sorogan, bandongan, bahtsul masail, and innovations in kitab kuning instruction. The findings reveal that pesantren have practically implemented the deep learning approach through various learning methods that demonstrate cognitive engagement, reflective awareness, and a joyful, contextual learning environment. These findings indicate that pesantren are capable of bridging classical Islamic pedagogical values with the demands of 21st-century educational transformation.